Exploring the mechanism of Schisandra rubriflora in the treatment of polycystic ovary syndrome based on network pharmacology and molecular docking - Zhengyan Dou; Qingxian Li; Jing Zhang; Xin Zhang (Journal of Ovarian Research)
Abstract Background Polycystic ovary syndrome (PCOS) is an endocrine disease associated with reproductive and metabolic abnormalities. The aim of this study was to elucidate the effects of Schisandra rubriflora (S. rubriflora) on PCOS and its related mechanisms using network pharmacology, molecular docking and in vitro experiments. Materials and methods HERB database and SwissTargetPrediction database were used to obtain the active components and the targets of S. rubriflora. Differentially expressed genes (DEGs) associated with PCOS were obtained by analyzing GSE54248 dataset. A protein-protein interaction network was constructed, and topological analyses were performed to identify the hub targets and main bioactive components. The binding abilities between hub targets and key components were studied by molecular docking. Finally, in vitro PCOS models were constructed with KGN cells and rat ovarian granulosa cells, respectively, and the regulatory effects of schisandrin, a key bioactive component of S. rubriflora, on the cells were investigated by in vitro assays. Results A total of 14 bioactive ingredients of S. rubriflora and 26 potential therapeutic targets of S. rubriflora in PCOS treatment were obtained. Bioinformatics analyses suggested that the mechanisms of S. rubriflora in treating PCOS were related to IL-17 signaling pathway and TNF signaling pathway. The binding affinities between key components of S. rubriflora (schisandrin, wyerone, and rugosal) and hub targets (PTGS2, MMP9, MCL1, and JUN) were high. Schisandrin could attenuate lipopolysaccharide-induced inflammation, oxidative stress, and apoptosis of KGN cells and rat ovarian granulosa cells, as well as inhibit hub target expression and TNF pathway activation. Conclusion PTGS2, MMP9, MCL1 and JUN are potential targets for S. rubriflora to treat PCOS. Schisandrin, a main component of S. rubriflora, may be a candidate for the treatment of PCOS. Graphical Abstract